Assertive Communication and Teamwork: Results of an Intervention Program to the Supervisors of a Company - Montes de Oca, Jesús H. (2014)
The study aimed to determine the effect of the implementation of the program "Manage your Talent" in competence assertive communication skills and teamwork. A quasi-experimental research design was used with pre-test - intervention - post-test with control group. The sample included 28 supervisors of a private company, 13 in the experimental group and 15 in the control group. A type of purposive sample was used. The results suggest a positive impact of the program to significantly increase competition achievement assertive communication (U = 3.5, Z = 4.58, *** P <.000), just as in effective dialogue dimensions (U = 8.0), feedback (U = 10.0), conflict resolution (U= 7.0) and non-verbal communication (U = 4.0), the skills of this competence in the highest increase was recorded were effective dialogue and nonverbal communication. In the other, the increase was lower. Regarding competition teamwork (U = 0.00, Z = 4.837, *** P <.000), just as in the dimensions (U = 9.0), Goal Achievement (U = 15.0), democratic environment (U= 12.0) and decision making (U = 7.0). The skills of this competence in the highest increase was recorded were the subject property, democratic environment and goal achievement. Minor increase in decision-making for managing consensus.